"They're younger… it's harder." Primary providers' perspectives on hypertension management in young adults: a multicenter qualitative study. (December 2017) - Johnson, Heather; Warner, Ryan; Bartels, Christie; LaMantia, Jamie
Abstract Background Young adults (18–39 year-olds) have the lowest hypertension control rates among adults with hypertension in the United States. Unique barriers to hypertension management in young adults with primary care access compared to older adults have not been evaluated. Understanding these differences will inform the development of hypertension interventions tailored to young adults. The goals of this multicenter study were to explore primary care providers' perspectives on barriers to diagnosing, treating, and controlling hypertension among young adults with regular primary care. Methods Primary care providers (physicians and advanced practice providers) actively managing young adults with uncontrolled hypertension were recruited by the Wisconsin Research & Education Network (WREN), a statewide practice-based research network. Semi-structured qualitative interviews were conducted in three diverse Midwestern clinical practices (academic, rural, and urban clinics) using a semi-structured interview guide, and content analysis was performed. Results Primary care providers identified unique barriers across standard hypertension healthcare delivery practices for young adults. Altered self-identity, greater blood pressure variability, and unintended consequences of medication initiation were critical hypertension control barriers among young adults. Gender differences among young adults were also noted as barriers to hypertension follow-up and antihypertensive medication initiation. Conclusions Tailored interventions addressing the unique barriers of young adults are needed to improve population hypertension control. Augmenting traditional clinic structure to support the "health identity" of young adults and self-management skills are promising next steps to improve hypertension healthcare delivery.